The use of index of orthodontic treatment need in an Iranian population - Hedayati Z; Fattahi H; Jahromi S (Wolters Kluwer Medknow Publications, 2007)
This study aims to evaluate the need for orthodontic treatment between 11 and 14 year old school children in Shiraz. A sample of 2000 students consisting of 1200 boys and 800 girls from various parts of the city was selected. The index of orthodontic treatment need (IOTN) was used by two calibrated examiners. The data was recorded in questionnaires to assess dental health components (DHC). Aesthetic components (AC) were evaluated both by students (AC) and examiners (ACE). The results for DHC of IOTN were: 18.39% of population showed severe and very severe need for treatment, 25.8% were in border line category, 48.1% had a slight need and the percentage for no need to treatment was 7.63%. In evaluating AC, 91.93% were in no need or little need, 3.91% in moderate need and 4.11% in great need to treatment group. Where as ACE resulted in: 91.31% no need and little need, 2.44% moderate need and 6.21% great need to treatment. There was a slight statistical correlation (0.54) between AC and ACE, but a very weak correlation between DHC and AC was observed. According to DHC, boys showed more need for treatment than girls (P=0.001). Grade 8 showed the most percentage in great need category in both AC and ACE (3.41% of 4.11% and 5.74% of 6.21%, respectively). The results indicate that the need for orthodontic treatment was less than other studies and most of the students were in the category of little need for treatment.